Al passivation effect at the HfO2/GaAs interface: A first-principles study. (January 2016) - Cai, Genwang; Sun, Qiang; Jia, Yu; Liang, Erjun
Abstract: III–V semiconductor interfacing with high-k dielectrics is critical for the high mobility metal oxide semiconductor field transistor (MOSFET) device. In this work, we utilize first-principles method to explore the electronic structures of the interface GaAs/HfO2 with the presence of Al interfacial defects. The simulation results indicate that Al substitutions & interstitials tend to increase the thermal stability of the interface. Meanwhile, this substitution removes the lower-half gap states of GaAs, partially passivating the interface and consequently suppressing the gap states. Also, we find that the band offset displays a dependence on the point defects of Al replacements of interfacial Hf and Ga.